Elderly’s Expectations of Services in Integrated Health Post (Posbindu): A Qualitative Study - Azana, Destyana Wulandari; Gondodiputro, Sharon; Didah, Didah (Majalah Kedokteran Bandung, 2019)
Many factors influence the compliance of the elderly to visit the Integrated Health Post (Posbindu). One factor that needs to be explored is the expectation of the elderly on the services in this post. Expectations that are met with performance will create satisfaction, leading to a regular visit to the Posbindu. This study aimed to explore the expectations of the elderly towards services provided in the Posbindu. A qualitative phenomenology study using a in-depth interview was conducted to 8 elderly informants from 7 Posbindu from 7 public health centers (Pusat Kesehatan Masyarakat, Puskesmas) who were selected by purposive sampling in Bandung City. Posbindu and Puskesmas was selected in a simple random manner. The study was conducted from July to October 2018. Explored concepts were structure, process, and output of expectations. The collected data was processed by coding and categorization.This study discovered that the structural expectation covered three subthemes, namely accessibility, human resources, and facilities. The process expectation was formed by three subthemes: behavior and communication skills of the cadres; behavior and communication skills of the health providers; consultation and treatment. The output expectation was formed by three categories, including information about their illness, controlled disease, and the desire to stay healthy. This study discovered 3 new categories from several subthemes of the health care provided in the Posbindu, i.e. free services, attendance of a doctor, and medicine prescription. In conclusion, the expectation of the elderly towards the health services at the Posbindu has been identified. Ekspektasi Lansia terhadap Pelayanan di Posbindu Banyak faktor yang mempengaruhi kepatuhan lansia untuk datang ke Pos Pembinaan Terpadu (Posbindu). Salah satu faktor yang perlu digali adalah harapan para lansia. Harapan sesuai dengan kenyataan akan menciptakan kepuasan, yang mengarah ke kunjungan rutin ke Posbindu. Tujuan dari penelitian ini adalah mengeksplorasi harapan para lansia terhadap layanan di Posbindu. Penelitian fenomenologis kualitatif dilakukan dengan menggunakan wawancara mendalam kepada 8 informan lansia dari 7 Posbindu (dari 7 Puskesmas) yang dipilih secara purposive sampling di Kota Bandung. Pemilihan Posbindu dan Puskesmas dilakukan secara acak sederhana. Studi ini dilakukan dari Juli hingga Oktober 2018. Konsep yang dieksplorasi adalah struktur, proses, dan output dari harapan. Data yang dikumpulkan, diproses dengan pengkodean dan kategorisasi. Penelitian ini menemukan harapan struktural dicakup oleh tiga sub-tema, yaitu aksesibilitas, sumber daya manusia, dan fasilitas. Harapan proses dibentuk oleh tiga sub-tema, yaitu perilaku dan komunikasi kader; perilaku dan komunikasi tenaga kesehatan; konsultasi dan perawatan. Harapan masukan dibentuk oleh tiga kategori, termasuk informasi tentang penyakit mereka, penyakit terkendali, dan keinginan untuk tetap sehat. Studi ini menemukan 3 kategori baru dari beberapa subtema yaitu tidak perlu membayar , kehadiran dokter, dan pemberian obat. Simpulan, harapan lansia terhadap layanan kesehatan di Posbindu telah diidentifikasi.